2021
DOI: 10.14341/probl12800
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical practice guidelines for hypoparathyroidism

Abstract: Hypoparathyroidism is a rare disorder characterized by the absent or inappropriately decreased serum parathyroid hormone in the parathyroid glands, which is accompanied by impaired calcium-phosphorus metabolism.The main etiology of hypoparathyroidism remains damage or removal of the parathyroid glands during neck surgery. In view of the incidence of thyroid cancer, primary hyperparathyroidism and other pathologies of the neck organs, which radical treatment can lead to the parathyroid gland impairment, an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
2
1
0
Order By: Relevance
“…Almost three-quarters of the included patients had 25(OH)D 3 levels in the target range (>30 ng/mL), which is slightly higher than the data from the federal registry [21,22] and consistent with some of the previous studies in hypoparathyroidism [23], though some of the studies showed higher levels of 25(OH)D [24]. It is worth noting that the recommended doses of cholecalciferol differ in the guidelines for the general population [17,18] and HypoPT patients [14,25]. The guidelines for HypoPT patients recommend cholecalciferol supplementations in a daily dose of 400-800 IU to the patients treated with activated vitamin D which, given our results, may not be enough to achieve the target range and may need to be revised.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Almost three-quarters of the included patients had 25(OH)D 3 levels in the target range (>30 ng/mL), which is slightly higher than the data from the federal registry [21,22] and consistent with some of the previous studies in hypoparathyroidism [23], though some of the studies showed higher levels of 25(OH)D [24]. It is worth noting that the recommended doses of cholecalciferol differ in the guidelines for the general population [17,18] and HypoPT patients [14,25]. The guidelines for HypoPT patients recommend cholecalciferol supplementations in a daily dose of 400-800 IU to the patients treated with activated vitamin D which, given our results, may not be enough to achieve the target range and may need to be revised.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, we assume that the abnormality of vitamin D metabolism does not interfere with the achievement of hypoparathyroidism compensation. We also found that magnesium levels were lower in nc-HypoPT, which highlights the importance of monitoring this parameter according to clinical guidelines [14,25].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation